Econometric modelling of issues in Caribbean economics and finance - Kim, Sang W. ed. (Caribbean Centre for Monetary Studies St. AugustineTT, 1998)
Includes papers presented or submitted for review at the Modelling Session of the 1996 and 1997 Annual Conferences of the Caribbean Centre for Monetary Studies.